Effective Strategies for Teaching Arabic Prosody in Oral Communication Skills - Nur Syukriyah Mohd Suib; Harun Baharudin (Qubahan Academic Journal)
An emphasis on the elements of prosody was crucial for achieving full proficiency in a spoken language. The research focused on prosody, which included components such as stress, intonation, pauses, and mora. This study aimed to evaluate the proficiency of Arabic teachers at Government Aided Religious Schools (SABK) in Selangor, Malaysia, regarding their understanding and instructional abilities in prosody, particularly in speaking skills. The study sample consisted of 152 Arabic teachers working at SABK in Selangor, Malaysia. The questionnaire was evaluated by four reviewers, and the results indicated a high level of reliability, as evidenced by Cronbach Alpha values of 0.91 for prosody teaching strategies and 0.90 for prosody knowledge. Both descriptive and inferential analyses were performed on the acquired data. The research data were analyzed using the Statistical Package for the Social Sciences (SPSS) software, version 20. The results of the data analysis showed that both the prosody knowledge (mean: 3.76, S.D.: 0.465) and the prosody teaching strategies (mean: 3.69, S.D.: 0.484) were at a relatively high level. According to Pearson's correlation analysis, there was a significant positive correlation (r=0.530) between the prosody teaching strategy and the prosody knowledge. Simultaneously, knowledge of prosody played an important role in applying prosody strategies effectively, contributing about 28.1 percent (r₂=0.281). Proficiency in Arabic prosody aided teachers in creating effective ways for two-way interaction inside the classroom. Students greatly benefited from this situation in terms of improving their communication skills, as it made class communication more effective. The Arabic language curriculum needed to provide teachers with training in prosody teaching strategies to enhance two-way communication in the classroom.